Analisis self-efficacy siswa sekolah menengah atas (SMA) dalam pembelajaran matematika di masa pandemi covid-19 - Mulyadi, Reza; Herizal; Fonna, Mutia (Jurnal Pendidik Indonesia, 2023)
The COVID-19 pandemic is an epidemic that has brought major changes to all aspects, including educational aspects. Different learning methods will affect several students' affective abilities, one of which is self-efficacy. The importance of this ability attracted researchers to conduct research aimed at describing aspects of students' self-efficacy in learning mathematics. The approach used is a quantitative approach, with the type of research being survey research. The population in this study were all class XI students in one of the state high schools in North Aceh Regency, with the sample being students in classes XI MIA 1, XI MIA 2, XI MIA 4, XI MIA 5, and XI IIS. The instrument used is a questionnaire. Data analysis was carried out descriptively, namely explaining students' self-efficacy abilities and determining students' self-efficacy categories using hypothetical mean categorization. The research results showed that 87.85% of students had self-efficacy in the medium category. This indicates that the majority of students keep trying and do not give up quickly on studying mathematics during COVID-19.